Interaksionisme Simbolik Pengguna Media Sosial Facebook dan WhatsApp Pada Isu Covid-19 - Zulkarnain Hamson (Journal of Communication Sciences (JCoS), 2020)
This research was conducted on WhatsApp and Facebook social media users, the aim of observing the behavior of the users of both social media, related to the issue of the pandemic Covid-19, which is sweeping the world. Indonesia is a country in the risk category, after a number of people with positive Covid-19 found. During the period March 10-17, 2020, conversations of members of the WhatsApp Group Alumni Association of the Faculty of Social and Political Sciences, Hasanuddin University, whose members tended to be heterogeneous, from various professional fields, were also spread throughout Indonesia, with more than 200 members and Lecturer groups FISIP University of Eastern Indonesia (UIT) Makassar, whose members tend to be homogeneous, and only resides in Makassar City. The Facebook group that was observed was a journalist group. It was revealed that Facebook and WhatsApp users were actively disseminating Covid-19 information in the form of religious propaganda, medical information, political responses, humorous humor. On both social media accounts, user behavior appears to be active, continuously informing the Cofid- 19 phenomenon, with various versions, including news links, opinions, analysis of both amateur and expert experts, criticism of the government, to memes and images that sometimes are photos of officials country. Research uses qualitative methods to explore and understand the meaning of messages. The approach and method of analysis used in this study are, content analysis method using quantitative data and qualitative data simultaneously.